MAXIMIZING PROMOTION MIX IN SHARIA BANKING TO INCREASE CUSTOMER'S DECISION-TO-SAVE - Mei Vita Hasti Liana; Rosana Eri Puspita; Mochlasin Mochlasin (IQTISHADUNA, 2021)
This study aims to determine the effect of the promotion mix on the customer's decision to save. This study uses quantitative methods by processing primary data. Data collection techniques by distributing questionnaires given to customers of Bank Syariah Indonesia in Central Java. Samples were taken as many as 96 respondents with non-probability sampling technique. The data obtained were then processed using the SPSS 25 analysis tool. The results showed that advertising partially had a significant negative effect on customer decisions, while sales promotion, personal selling, direct marketing, and public relations variables partially had a significant positive effect on customer decisions. Together or simultaneously there is an influence between advertising, sales promotion, personal selling, direct marketing, and public relations on the customer's decision to save in Bank Syariah Indonesia (BSI). Researchers hope that BSI can improve promotional strategies, especially in advertising so that it is packaged as attractively as possible so that customers get more complete information, are interested, and then decide to become customers of Bank Syariah Indonesia